2011
DOI: 10.1007/s00595-010-4333-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolated tuberculous liver abscess invading the abdominal wall: Report of a case

Abstract: Isolated tuberculous liver parenchymal and subcapsular abscesses are unusual,^but an abdominal wall abscess secondary to a tubercular liver abscess is extremely rare. To our knowledge, there is only one reported case of an abdominal wall abscess occurring secondary to a subcapsular liver abscess. We report the first documented case of direct invasion of the abdominal wall from an isolated tuberculous liver parenchymal abscess, diagnosed by imaging, surgical, and pathological findings. Although ultrasonography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The portal vein showed dilation as well to mononuclear leukocyte infiltration and congestion of the hepatic sinusoids, in addition to high proliferation and hyperplasia of the epithelial cells of the bile ducts and hepatic artery followed by fibrous capsule infiltrated with leucocytes. These results was followed those obtained previously [22] who are isolated tuberculous liver parenchymal and sub-capsular abscesses. In the present study, the abscess capsule showed severe infiltration of polymorphonuclear cells infiltration mainly neutrophils especially around the abscess capsules; Also there was a severe abscessation surrounded by inflammatory zone like a capsule.…”
Section: Discussionsupporting
confidence: 87%
“…The portal vein showed dilation as well to mononuclear leukocyte infiltration and congestion of the hepatic sinusoids, in addition to high proliferation and hyperplasia of the epithelial cells of the bile ducts and hepatic artery followed by fibrous capsule infiltrated with leucocytes. These results was followed those obtained previously [22] who are isolated tuberculous liver parenchymal and sub-capsular abscesses. In the present study, the abscess capsule showed severe infiltration of polymorphonuclear cells infiltration mainly neutrophils especially around the abscess capsules; Also there was a severe abscessation surrounded by inflammatory zone like a capsule.…”
Section: Discussionsupporting
confidence: 87%
“…Tuberculous abscesses may appear as hyperechoic solid lesions and may mimic a neoplastic disease [52]. CT shows fluid or pus collection in the liver parenchyma with an associated thick enhancing wall [61] (Fig. 8).…”
Section: Macroscopic Mass-forming Localized Hepatic Tuberculosismentioning
confidence: 99%
“…Primary tubercular liver abscess (TLA) is an extremely rare condition, even in countries such as India, where TB is highly prevalent 2,3. Liver abscesses in portal cavernoma cholangiopathy (PCC) are predominantly pyogenic due to associated cholangitis.…”
Section: Introductionmentioning
confidence: 99%